Perlindungan Hukum Bagi Transgender Sebagai Warga Binaan Pemasyarakatan - Philippa Philomena Kosho; Deassy Jacomina Anthoneta Hehanussa; Yonna Beatrix Salamor (Faculty of Law, Universitas Pattimura, 2021)
Introduction: Transgender is a term used to describe people who behave differently or appear to not match their gender. Regulations for the protection of transgender people in Indonesia do not exist hence cases pertaining transgender people are not clearly regulated. Purposes of the Research: The purpose of this study is to examine and analyze the position of transgender people as correctional residents and to examine and analyze legal protection for transgender as correctional residents.Methods of the Research: The type of legal research used is normative juridical. This type of research is conducted through a process of finding the rule of law, legal principles and legal doctrines to answer legal issues faced or research that refers to the norms found in the legislation. This research uses a statute and comparative approach.Results of the Research: This research concluded that the position of transgender people as correctional residents in Indonesia until now is not clear. The classification of correctional residents in prisons is based on sex identification (male and female) not gender qualifications hence that the position and development of transgender people is still equated with other correctional residents. In addition to this, until now there has been no specific picture of legal protection for transgender people as correctional residents due to the legal vacuum regarding transgender protection in Indonesia.